Relaciones públicas en la imagen corporativa de la empresa CODEVSA de la ciudad de Riobamba - Yesenia Paulina, Huanca Guaño (2021)
ABSTRACT The company CODEVSA of Riobamba city has been performing its services anonymously despite not having a corporate image and not having communication channels to reach external customers, making its corporate image not known. The lack of knowledge of public relations strategies has prevented the company from positioning itself in the market, limiting the fulfillment of the objectives set by the company. The company provides its services in training and advice on industrial safety and occupational hygiene, where public relations play a significant role so that the corporate image is made known and thus the services that the company provides are hired.The descriptive method is used in this research that seeks to specify, identify, and evaluate specific criteria and problems that a company has. This method has the following phases: The problem statement; Hypothesis formulation, deductions, and consequences of the hypothesis; and verification and verification of the hypothesis. The results that I obtained in the investigation allowed me to affirm the existing problems in the CODEVSA company, thus establishing that PR has a significant impact on the company's corporate image. Keywords: Public Relations -Strategies -Loyalty -Positioning in the market. Translation reviewed by: Msc. Elizabeth Diaz English Professor c.c. 0603277765